Expression of nodal signalling components in cycling human endometrium and in endometrial cancer - Makanji Yogeshwar; Lackmann Martin; Wang Fang; Nicholls Peter K; Papageorgiou Irene; Salamonsen Lois A; Robertson David M; Harrison Craig A (BMC, 2009)
Abstract Background The human endometrium is unique in its capacity to remodel constantly throughout adult reproductive life. Although the processes of tissue damage and breakdown in the endometrium have been well studied, little is known of how endometrial regeneration is achieved after menstruation. Nodal, a member of the transforming growth factor-beta superfamily, regulates the processes of pattern formation and differentiation that occur during early embryo development. Methods In this study, the expression of Nodal, Cripto (co-receptor) and Lefty A (antagonist) was examined by RT-PCR and immunohistochemistry across the menstrual cycle and in endometrial carcinomas. Results Nodal and Cripto were found to be expressed at high levels in both stromal and epithelial cells during the proliferative phase of the menstrual cycle. Although immunoreactivity for both proteins in surface and glandular epithelium was maintained at relatively steady-state levels across the cycle, their expression was significantly decreased within the stromal compartment by the mid-secretory phase. Lefty expression, as has previously been reported, was primarily restricted to glandular epithelium and surrounding stroma during the late secretory and menstrual phases. In line with recent studies that have shown that Nodal pathway activity is upregulated in many human cancers, we found that Nodal and Cripto immunoreactivity increased dramatically in the transition from histologic Grade 1 to histologic Grades 2 and 3 endometrial carcinomas. Strikingly, Lefty expression was low or absent in all cancer tissues. Conclusion The expression of Nodal in normal and malignant endometrial cells that lack Lefty strongly supports an important role for this embryonic morphogen in the tissue remodelling events that occur across the menstrual cycle and in tumourogenesis.